ANALISIS RASIO KEUANGAN DALAM MEMPREDIKSI FINANCIAL DISTRESS PADA NASABAH KREDIT PT. BANK MEGA Tbk. CABANG PURWOKERTO - Carolina Ety Widjayanti (Majalah Imiah Manajemen & Bisnis, 2020)
Increased competition in the banking world, the soundness of a bank to be a priority for customers in choosing a bank before they put down deposits. Therefore, the bank must increasingly have the creativity of a revolving fund that is managed dihimpunnya to gain advantages, one of them in the form of credit. For that banks are required to maintain public confidence and maintain the liquidity risk, that is not shackled with the issue of problem loans. The quality of the prospective customer a credit note by analyzing the financial condition of prospective customers and prospective customers predicting bankruptcy of credit. The purpose of this research is done because of the growing number of non-performing loans (NPLs) increased net nationally, is expected to use the Altman Z-Score, the banks can detect early clients or potential clients who experienced Financial Disstress¸sehingga credit can be decided in lending as well as policies to monitor customers' business continuity, especially in financial matters. This research uses descriptive analysis and hypothesis testing with a case in PT.Bank Mega Tbk. Branch Purwokerto. The following hypothesis testing first hypothesis is accepted if -rata average Z-Score <1.23 and second hypothesis is accepted if the Z-score> 2.90. Data taken using the method of documentation is to examine and review the records and financial statements of the company. The research result was a conclusion that the conditions of credit customers PT.Bank Mega Tbk Branch Purwokerto whether included in the category Current and Special Mention, the average financial ratios of 2014 and 2015 is quite good; almost all credit customers are included in Special Mention (DPK) experienced Financial Distress, with an average Z-Score is the gray area that is 1.23 <Z <2.90 while credit customers who fall into predictable Fluent quality not experienced Financial distress, with an average value of Z-score> 2.90. Keyword : Financial Ratio, Financial Distress